Serum apelin levels in patients with thyroid dysfunction - Gurel, Ali; Dogantekin, Akif; Ozkan, Yusuf; Aydin, Suleyman (E-Century Publishing Corp, 2015)
Adipocytes are not only for energy storage, but are also functionally active cells, producing biologically active peptides called adipocytokines. Adipocytokines control nutrition, thermogenesis, immunity, thyroid and reproductive hormones, and neuroendocrine functions. One of the most important new members of this family is apelin. In patients with thyroid dysfunctions, there are usually changes in weight, thermogenesis and adipose tissue lipolysis. Here, we investigated the serum apelin levels in different thyroid hormone states. Our study group consisted of the following patients: 32 thyrotoxicosis, 32 subclinical hyperthyroidism, 31 hypothyroidism, 34 subclinical hypothyroidism and 31 healthy control cases. In addition to routine blood tests, serum free 13 (FT3), free 14 (FT4), TSH and apelin levels were measured, and the body mass index (BMI) was recorded. In terms of the demographic characteristics, age and BMI, there was no statistically significant difference between the groups (P>0.05). The mean serum apelin levels of the groups were as follows: thyrotoxicosis group, 4.6 1.9 ng/ml; subclinical hyperthyroidism group, 3.7 1.9 ng/mi; hypothyroid group, 4.8 2.5 ng/mi; subclinical hypothyroidism group, 4.3 2.2 ng/mL; and control group, 3.4+1.4 ng/ml, respectively. There was no statistically significant difference in terms of the mean apelin levels between the groups (P>0.05). The hypothyroid group had the highest and the control group had the lowest mean apelin levels. As a result, the apelin levels were higher in both the patients with hypothyroidism and hyperthyroidism, in comparison with the normal population, but without statistical significance.
Keywords: Thyroid dysfunction; apelin; metabolic disorders